Túa BLESA, "Maurice Blanchot. La pasión del errar", Barcelona, Edicions Universitat de Barcelona (“Figura”), 2020, 300 pp. - Hidalgo, Max (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Túa Blesa, Maurice Blanchot. La pasión del errar, Barcelona, Edicions Universitat de Barcelona (“Figura”), 2020, 300 pp.